2015
DOI: 10.1007/s10955-015-1332-8
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs in Delayed Information Transmission in Biochemical Networks

Abstract: In order to transmit biochemical signals, biological regulatory systems dissipate energy with concomitant entropy production. Additionally, signaling often takes place in challenging environmental conditions. In a simple model regulatory circuit given by an input and a delayed output, we explore the trade-offs between information transmission and the system's energetic efficiency. We determine the maximally informative network, given a fixed amount of entropy production and delayed response, exploring both the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Knowing the fundamental thermodynamic limits on sensor operation is also relevant to the engineering of synthetic sensors. Drawing on the connections between information and thermodynamics, several groups have considered the intrinsic costs associated with sensing and adaption (sensors that adapt revert to zero after lengthy exposure to a constant input) [12,13,[22][23][24][25][26][27][28][29][30][31]. For example, Govern and ten Wolde showed that molecular readout molecules of cell-surface receptors must consume free energy to form long-lived memories of receptor states [26,27], a process equivalent to thermodynamic measurement of the kind performed by Maxwell's demon [13].…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the fundamental thermodynamic limits on sensor operation is also relevant to the engineering of synthetic sensors. Drawing on the connections between information and thermodynamics, several groups have considered the intrinsic costs associated with sensing and adaption (sensors that adapt revert to zero after lengthy exposure to a constant input) [12,13,[22][23][24][25][26][27][28][29][30][31]. For example, Govern and ten Wolde showed that molecular readout molecules of cell-surface receptors must consume free energy to form long-lived memories of receptor states [26,27], a process equivalent to thermodynamic measurement of the kind performed by Maxwell's demon [13].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade many studies have addressed this issue within an information theoretic framework in different contexts [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The general idea behind this line of work is that optimal effectiveness of a regulatory module is achieved when the mutual information between input and output nodes is maximized.…”
Section: Introductionmentioning
confidence: 99%
“…But such general frameworks are lacking for understanding the dynamics of an important class of systems -networks of cells such as tissues and biofilms in which multiple cells, without any morphogen gradients, collectively generate spatial patterns by regulating each other's genes with diffusing chemicals and genetic circuits 9 . Indeed, it is unclear if and how principles such as information-optimization 12 and metrics such as thermodynamic potentials, despite their utility in other contexts [13][14][15][16][17][18][19] , apply to spatiotemporal gene regulations by hundreds of cells. Moreover, we usually do not know which metrics suitably describe these systems.…”
mentioning
confidence: 99%
“…Until now, we have analysed deterministic cellular automata. But real cells are noisytheir gene expressions are stochastic 1,[8][9][10][12][13][14][15][16]18,19 . We can treat such biological noise by having the secretion rate and the threshold K to fluctuate over time for each cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation